A Nonlinear Dynamic Foundation Model for Dynamic Response of Track-Train Interaction - Phuoc T. Nguyen; Trung D. Pham; Hoa P. Hoang (Shock and Vibration)
The paper studies the dynamic response of track-train interaction on a nonlinear dynamic foundation model with special things such as (i) the nonlinear dynamic foundation model includes a nonlinear elastic spring, shear layer, viscous damping, and foundation mass; (ii) the process of the finite-element method of nonlinear dynamic response of the foundation and track-train interaction is established clearly; (iii) the numerical results show that the foundation mass has a significant effect on the dynamic characteristic of the structure system and dynamic response of track-train interaction under a moving vehicle and almost have more increasing dynamic displacements than others without the effect of the foundation mass. Therefore, it can be seen that the study has meaning practice, and the foundation quite agrees to describe the true behaviour of soil in the problems of the dynamic response of structures on the foundation.